Reliable software technologies – Ada-Europe 2017 : 22nd Ada-Europe International Conference on Reliable Software Technologies, Vienna, Austria, June 12-16, 2017, Proceedings /: 22nd Ada-Europe International Conference on Reliable Software Technologies, Vienna, Austria, June 12-16, 2017, Proceedings. (2017) - Unknown
No abstract available